VETERINARY AND SANITARY EVALUATION OF CHICKEN MEAT WHEN USING FEED MINERAL CONCENTRATE "NATURAL ZEOLITE" IN THE DIET - Lozowicka, B.; Paritova, A. Y.; Kushmukhanov, Zh. S.; Nakhatova, N. K. (Ғылым және білім=Наука и образование=Science and education - № 4-1 (69), 2022)
The zeolite used in this experiment contains at least 81% clinoptilolite. It also contains 62% SiO2, 16% Al2O3, 5.45% Fe2O3 and 5.12% CaO, 2.30% MgO, 2.62% K2O and 2.03% NaO (Table 2). Organoleptic examination revealed that carcasses of 10, 20 and 30-day-old chickens raised with feed additive had no foreign smell, the appearance of the carcass did not change in comparison with the carcasses of the control group. The color is pale pink, slightly moist, did not leave wet spots on the filter paper. When cooking meat, the soup turned out to be transparent, fragrant, and pleasantly smelling. The pH content of chicken meat in the research group was 5.8-6.0, which corresponded to the pH of ripe, raw meat. The activity of peroxidase in the muscles of experimental and control chickens was the same. No ammonia and ammonium salts were found in the studied samples of poultry meat of the control and experimental groups. The content of amino-ammiac nitrogen in muscles of the studied chickens was 1.07 - 1.11 mg. The number of mesophilic aerobic and facultative anaerobic microorganisms (NMAFAnM) was 6.5×103-1.0×104. Pathogens, including salmonella and listeria monocytogens, were not isolated in 25 g of the product. The nutritional value of meat in 100 g of the product was 132.6 kcal in 10-day chicken meat; 137.9 kcal in 20-day chicken meat; 143.1 kcal in 30-day chicken meat.В данной статье изучены качественные показатели мяса кур при использовании в их рационе кормового минерального концентрата «Цеолит натуральный». Цель исследования - дать ветеринарно-санитарную оценку куриного мяса при добавлении в рацион «Цеолит натуральный». Исследования проводились на 120 суточных цыплятах Росс 90, принадлежащих птицефабрике «Курица Ряба» в 2021-2022 гг. Цеолит, использованный в этом эксперименте, содержит не менее 81% клиноптилолита. Он также содержит 62 % SiO2, 16 % Al2O3, 5,45 % Fe2O3 и 5,12 % CaO, 2,30 % MgO, 2,62 % K2O и 2,03 % NaO (табл. 2). Органолептическое исследование показало, что тушки 10, 20 и 30-дневных цыплят, выращенных с кормовой добавкой, не имели постороннего запаха, внешний вид тушки не изменился по сравнению с тушами контрольной группы. Цвет бледно-розовый, слегка влажный, на фильтровальной бумаге мокрых пятен не оставил. При варке мяса суп получился прозрачным, ароматным, приятно пахнущим. Содержание рН куриного мяса в опытной группе составляло 5,8-6,0, что соответствовало рН созревшего, сырого мяса. Активность пероксидазы в мышцах опытных и контрольных цыплят была одинаковой.
Keywords: научный журнал; ринц; отечественное издание; периодическое издание; журнал коксон; птицеводство; кормление птиц; рацион птиц; feed additives; veterinary-sanitary evaluation; chicken meat; мясо кур